Development of a checklist to aid in the assessment of 'failure to return' from approved leave by acute inpatients. (25th May 2019) - Meehan, Tom; Mansfield, Yolanda; Stedman, Terry
Abstract: Better assessment of consumer behaviour and intentions prior to the granting of approved leave may reduce failure to return from such episodes of leave. The aims of this study were (i) to gain consensus on the factors associated with failure to return, and (ii) use these factors to construct a checklist to aid in assessment of consumers prior to being granted leave. Following a review of the literature a pool of 36 factors was identified. These were then assessed for relevance to absconding from approved leave using a modified Delphi approach. After two Delphi rounds, 10 factors were retained and these were collapsed under 6 domains; history of absconding, current substance use, behaviour cues, verbal cues, lack of engagement, and changes in mental state. While staff reactions to the checklist were positive, further testing of its effectiveness in the clinical setting is required.